3D tumor spheroids: an overview on the tools and techniques used for their analysis - Costa, Elisabete Cristina da Rocha (2018)
In comparison with 2D cell culture models, 3D spheroids are able to accurately mimic some features of solid tumors, such as their spatial architecture, physiological responses, secretion of soluble mediators, gene expression patterns and drug resistance mechanisms. These unique characteristics highlight the potential of 3D cellular aggregates to be used as in vitro models for screening new anticancer therapeutics, both at a small and large scale. Nevertheless, few reports have focused on describing the tools and techniques currently available to extract significant biological data from these models. Such information will be fundamental to drug and therapeutic discovery process using 3D cell culture models. The present review provides an overview of the techniques that can be employed to characterize and evaluate the efficacy of anticancer therapeutics in 3D tumor spheroids.